Handbook of early childhood education - Pianta, Robert C., 1956-? (New York Guilford Press, 2012)
Comprehensive and authoritative, this forward-thinking book reviews the breadth of current knowledge about early education and identifies important priorities for practice and policy. Robert C. Pianta and his associates bring together foremost experts to examine what works in promoting all children's school readiness and social-emotional development in preschool and the primary grades. Exemplary programs, instructional practices, and professional development initiatives?and the systems needed to put them into place?are described. The volume presents cutting-edge findings on the family and social context of early education and explores ways to strengthen collaboration between professionals and parents.
Keywords: Niños -- Desarrollo; Evaluación educativa; Libros electrónicos